Monolithic supported palladium-based catalyst as well as preparation method and application thereof

By growing metal magnesium on the foamed nickel NF support and loading palladium, an integral supported palladium-based catalyst was prepared, which solved the problem of easy sintering of palladium-based catalysts under high temperature conditions, and achieved high dispersion, low temperature activity and thermal stability. It was suitable for catalytic combustion of low concentration methane.

CN119657167AActive Publication Date: 2025-03-21CHONGQING UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411828346.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-21
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

Existing palladium-based catalysts are prone to sintering under high temperature conditions, resulting in reduced catalytic activity and thermal stability, making it difficult to effectively remove low concentrations of methane.

Method used

Using an integral supported palladium-based catalyst, high dispersion and stability of palladium are achieved by growing metal magnesium on foam nickel NF support, and Mg-NF matrix is ​​formed, and palladium is supported on the matrix.

Benefits of technology

The thermal stability and low-temperature catalytic activity of the catalyst are improved, the agglomeration and growth of palladium elements are prevented, and the complete conversion of methane at lower temperatures (such as 450°C) is achieved. The catalyst has good reactivity and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657167A_ABST
    Figure CN119657167A_ABST
Patent Text Reader

Abstract

The invention relates to an integral supported palladium-based catalyst and a preparation method and application thereof, and relates to the technical field of catalysts, the catalyst is composed of a carrier foamed nickel (NF), a noble metal palladium (Pd) and another metal for catalyst surface modification, the typical modified metal is magnesium (Mg), and the typical modified metal is magnesium (Mg). According to the preparation process, metal magnesium grows on NF to form a firm Mg-NF matrix, then palladium is loaded on the matrix, and the integral supported palladium-based catalyst Pd / Mg-NF is prepared, the method is simple in preparation, mild in condition, controllable in process and high in repeatability, and the product has good reaction activity and stability and has good practical application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst technology, and in particular to an integral supported palladium-based catalyst and a preparation method and application thereof. Background Art

[0002] As the energy shortage problem becomes increasingly serious, natural gas is widely used in natural gas vehicles and urban heating due to its abundant reserves, low price, convenient use and high thermal efficiency. Methane (CH4) is one of the main components of natural gas, providing a large amount of energy and heat for our daily life. However, the greenhouse effect of methane is much higher than that of CO2, so how to effectively control its emissions, especially the emission of low-concentration CH4 gas, has become one of the issues worthy of attention.

[0003] Methane is one of the most stable alkanes in terms of chemical structure. The direct combustion method requires extremely high reaction temperature, and this process will produce incidental incomplete combustion products (CO, NO x ), which not only wastes a lot of energy, but also causes secondary pollution to the environment. In order to achieve more efficient removal of low-concentration methane while reducing energy use, catalytic combustion technology is needed. The key to this technology lies in the development of catalytic combustion catalysts with high activity, thermal shock resistance, and high temperature resistance.

[0004] The commonly used methane catalytic combustion catalysts at present include precious metal catalysts and transition metal oxide catalysts, wherein palladium-based catalysts are generally recognized catalysts with higher methane low-temperature oxidation activity. The Chinese patent with publication number CN103131488A discloses a catalyst for low-concentration methane catalytic combustion and a preparation method thereof, wherein the catalyst comprises catalytically active components (Pd, Pt, Ru, Rh, etc.), catalyst carrier Al2O3 and metal oxide co-carriers (Mg, La, Fe, Mn, Ni, Co, etc.), utilizing any one of the methods of impregnation, homogeneous precipitation, coprecipitation, and thermal decomposition, the performance of the prepared catalyst is compared with the palladium catalyst without adding an auxiliary agent, the activity and stability are greatly improved, but the methane complete purification temperature still needs to reach more than 600°C, and palladium nanoparticles are easily sintered under high temperature conditions, thereby causing the activity and thermal stability of the catalyst to be reduced. Summary of the invention

[0005] The purpose of the present invention is to address the above-mentioned problems and to provide an integral supported palladium-based catalyst for catalytic combustion of methane, which disperses and stabilizes the precious metal palladium through the strong interaction between a specific carrier and the metal active component, while promoting its high dispersion and improving the low-temperature catalytic activity, and can prevent the agglomeration and growth of the metal components, and has both good reaction activity and stability.

[0006] The first aspect of the present invention provides a method for preparing a monolithic supported palladium-based catalyst, which comprises first growing metallic magnesium on NF to form a Mg-NF matrix, and then loading palladium on the matrix to prepare a monolithic supported palladium-based catalyst Pd / Mg-NF, comprising the following steps:

[0007] S1. NF carrier pretreatment: select an appropriate amount of NF raw material and clean the oil impurities on the surface, and then dry to obtain the treated NF carrier;

[0008] S2. Preparation of Mg-NF matrix: The NF carrier obtained in S1 is mixed with a metal Mg salt solution and a precipitant, and the mixed solution is placed in an oven for reaction, and taken out after natural cooling, and dried to obtain a Mg-NF matrix;

[0009] S3, preparation of Pd / Mg-NF: The Mg-NF matrix obtained in S2 is mixed with a metal Pd salt solution and a precipitant, and the mixed solution is placed in an oven for hydrothermal reaction, and taken out after natural cooling, and dried to obtain an integral supported palladium-based catalyst Pd / Mg-NF.

[0010] By adopting the above technical scheme, nickel foam NF is selected as a specific carrier, which has low cost and good thermal conductivity, thermal stability and a porous structure with a high surface area, providing a uniformly distributed space for the subsequent loading of precious metal palladium. The nickel foam is modified by a metal magnesium solution, which can effectively prevent the spontaneous agglomeration of palladium elements, so as to improve the subsequent dispersibility of palladium and improve the thermal stability of the catalyst, which is beneficial to improve the atomic utilization efficiency of active components and realize the catalytic conversion of methane at low temperature with a lower precious metal loading. The precious metal palladium is dispersed and stabilized through the strong interaction between the specific carrier and the metal active component, which can prevent the agglomeration and growth of the metal components while promoting its high dispersion and improving the low-temperature catalytic activity. The product has both good reaction activity and stability.

[0011] Preferably, the preparation method comprises the following steps:

[0012] S1. NF carrier pretreatment: select NF disc raw material with a diameter of 32mm and a thickness of 1mm, immerse it in an acetone solution for ultrasonic treatment for 10-30min, then take out the NF and wash it with deionized water, then place the NF in a hydrochloric acid solution with a concentration of 0.2-2mol / L and ultrasonically treat it for 2-20min, then take out the NF and wash it with deionized water, finally place the NF in an anhydrous ethanol solution for ultrasonic treatment for 10-30min to clean the oil impurities on the surface, and dry it in an oven at 60-90℃ for 1-5h to obtain the treated NF carrier;

[0013] S2, preparation of Mg-NF matrix: take 1-10 pieces of NF carrier obtained in S1 and place them in a hydrothermal reactor, prepare a modified mixed solution of metal Mg salt solution and precipitant, add the modified mixed solution into the hydrothermal reactor for ultrasonic mixing for 10-30 minutes, then place the hydrothermal reactor in a 100-200°C oven for reaction for 1-10 hours, cool naturally after the reaction is completed, wash the cooled product and place it in a 60-90°C oven for drying, and dry it for 1-5 minutes to obtain a Mg-NF matrix, wherein the modified mixed solution is prepared as follows: 0.1-1mmol of metal Mg salt solution and 0.5-2mmol of precipitant are dissolved in 60-90mL of deionized water, wherein the metal Mg salt solution is a magnesium nitrate solution, and the precipitant is a urea solution;

[0014] S3, preparation of Pd / Mg-NF: placing the Mg-NF matrix obtained in S2 in a hydrothermal reactor, preparing a loaded mixed solution of a metal Pd salt solution and a precipitant, adding the loaded mixed solution into the hydrothermal reactor for ultrasonic mixing for 10-30 minutes, and then placing the hydrothermal reactor in a 100-200°C oven for reaction for 1-10 hours. After the reaction is completed, the reaction is naturally cooled. After washing the cooled product, it is transferred to a 60-90°C oven for drying. After drying for 1-5 hours, an integral loaded palladium-based catalyst Pd / Mg-NF is obtained. The loaded mixed solution is prepared as follows: 1.5-4.5 ml of a metal Pd salt solution and 0.5-2 mmol of a precipitant are dissolved in 60-90 mL of deionized water, wherein the metal Pd salt solution is a palladium nitrate solution, and the precipitant is a urea solution.

[0015] Preferably, in the above-mentioned preparation method technical scheme, the step S1 is specifically as follows: S1, NF carrier pretreatment: select NF disc raw material with a diameter of 32 mm and a thickness of 1 mm, immerse it in an acetone solution for ultrasonic treatment for 20 minutes, then take out the NF and rinse it with deionized water for 5 times, then place the NF in a hydrochloric acid solution with a concentration of 1 mol / L and ultrasonically treat it for 10 minutes, then take out the NF and wash it with deionized water, and finally place the NF in an anhydrous ethanol solution for ultrasonic treatment for 20 minutes to clean the oil impurities on the surface, and dry it in an oven at 75°C for 3 hours to obtain the treated NF carrier.

[0016] Preferably, in the above-mentioned preparation method technical scheme, the step S2 is specifically as follows: S2, preparation of Mg-NF matrix: take 5 pieces of NF carrier obtained in S1 and place them in a hydrothermal reactor with a volume of 100 ml, prepare a modified mixed solution of metal Mg salt solution and precipitant, add the modified mixed solution into the hydrothermal reactor for ultrasonic mixing for 20 minutes, and then place the hydrothermal reactor in a 160°C oven for reaction for 6 hours. After the reaction is completed, it is naturally cooled. After the cooled product is washed, it is placed in an oven at 75°C for drying for 3 hours. After drying, the Mg-NF matrix is ​​obtained. The configuration method of the modified mixed solution is as follows: after mixing 0.5 mmol of magnesium nitrate solution and 1.5 mmol of urea solution, deionized water is added to make the volume to 80 mL.

[0017] Preferably, in the above-mentioned preparation method technical scheme, the step S3 is specifically as follows: S3, Pd / Mg-NF preparation: Take 5 pieces of Mg-NF matrix obtained in S2 and place them in a hydrothermal reactor with a volume of 100 ml, prepare a loaded mixed solution of metal Pd salt solution and precipitant, add the loaded mixed solution into the hydrothermal reactor for ultrasonic mixing for 20 minutes, and then place the hydrothermal reactor in a 160°C oven to react for 6 hours. After the reaction is completed, it is naturally cooled. After the cooled product is washed, it is transferred to a 75°C oven and dried for 3 hours. After drying, an integral supported palladium-based catalyst Pd / Mg-NF is obtained. The configuration method of the loaded mixed solution is as follows: After mixing 3 mL of palladium nitrate solution and 1.5 mmol of urea solution, deionized water is added to make the volume to 80 mL.

[0018] Preferably, in S2, the magnesium nitrate solution is obtained by dissolving 0.1282 g of magnesium nitrate hexahydrate in deionized water.

[0019] Preferably, in S3, the palladium nitrate solution is obtained by dissolving 1 g of palladium nitrate dihydrate in 500 g of deionized water.

[0020] Preferably, in S3, the urea solution is obtained by dissolving 1.8021 g of urea in deionized water.

[0021] By adopting the above technical scheme, the specific steps of the preparation method are optimized to obtain a supported palladium-based catalyst with better performance.

[0022] The second aspect of the present invention provides a monolithic supported palladium-based catalyst obtained by any of the preparation methods described above.

[0023] The third aspect of the present invention provides the use of the above-mentioned integral supported palladium-based catalyst in the catalytic combustion treatment of methane.

[0024] In summary, the present application includes at least one of the following beneficial technical effects:

[0025] 1. Nickel foam NF is selected as a specific carrier. It has low cost, good thermal conductivity, thermal stability and a porous structure with a high surface area, which provides a uniformly distributed space for the subsequent loading of precious metal palladium. Modifying the nickel foam by metal magnesium solution can effectively prevent the spontaneous agglomeration of palladium elements, so as to improve the subsequent dispersibility of palladium and improve the thermal stability of the catalyst, which is beneficial to improve the atomic utilization efficiency of active components and realize the catalytic conversion of methane at low temperature with a lower precious metal loading. The precious metal palladium is dispersed and stabilized through the strong interaction between the specific carrier and the metal active component, which can prevent the agglomeration and growth of the metal component while promoting its high dispersion and improving the low-temperature catalytic activity. The product has both good reaction activity and stability.

[0026] 2. The catalyst prepared by this method is used for the catalytic combustion reaction of methane, and the complete conversion of methane can be achieved at around 450°C.

[0027] 3. The preparation method is simple, the conditions are mild, the process is controllable, the repeatability is strong, and it has good practical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a comparison curve of the conversion rates of Examples 1-3 in the present application at the same methane concentration;

[0029] Figure 2 is a conversion rate curve diagram of Example 2 of the present application at different methane concentrations;

[0030] Figure 3 is a graph showing the conversion rate of NF of the present application, Example 2 and Comparative Example 1 at a methane concentration of 1 vol%;

[0031] Figure 4 is a graph showing the conversion rate of the catalysts of Example 2 and Comparative Examples 2-4 of the present application at a methane concentration of 1 vol%;

[0032] Figure 5 It is a physical picture of the catalyst of NF, Example 2 and Comparative Examples 1-4 of the present application;

[0033] Figure 6 This is the SEM-EDS image of Example 2 of the present application before use;

[0034] Figure 7 This is the SEM-EDS image after use of Example 2 of the present application;

[0035] Figure 8 is the SEM image of Example 2 of the present application before and after use;

[0036] Fig. 9 It is a comparison chart of the thermal stability of the catalysts of Example 2 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0038] The information of reagents, instruments and equipment used in the following examples is shown in Tables 1.1 and 1.2. All reagents and chemicals were used as they are without further treatment. Other specific conditions not specified were carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0039] Table 1.1 Information of reagents used

[0040]

[0041] Table 1.2 Information of instruments and equipment used

[0042]

[0043] 1. Implementation

[0044] Example 1

[0045] A method for preparing a monolithic supported palladium-based catalyst comprises the following steps:

[0046] S1. NF carrier pretreatment: select NF disc raw material with a diameter of 32 mm and a thickness of 1 mm, immerse it in an acetone solution for ultrasonic treatment for 10 minutes, then take out the NF and rinse it with deionized water for 5 times, then place the NF in a hydrochloric acid solution with a concentration of 0.2 mol / L and ultrasonically treat it for 2 minutes, then take out the NF and rinse it with deionized water for 5 times, finally place the NF in an anhydrous ethanol solution for ultrasonic treatment for 10 minutes to clean the oil impurities and residual substances on the surface, and dry it in an oven at 60°C for 1 hour to obtain the treated NF carrier, wherein the acetone solution, hydrochloric acid solution, and anhydrous ethanol solution are directly used as the corresponding products purchased without further treatment.

[0047] S2. Preparation of Mg-NF matrix: Take one piece of NF carrier obtained in S1 and place it in a hydrothermal reactor with a volume of 100 ml, prepare a modified mixed solution of metal Mg salt solution and precipitant, add the modified mixed solution into the hydrothermal reactor for ultrasonic mixing for 10 minutes, and then place the hydrothermal reactor in a 100°C oven to react for 1 hour. After the reaction is completed, cool it naturally. After the cooled product is washed, place it in an oven at 60°C and dry it for 1 hour to obtain the Mg-NF matrix.

[0048] The modified mixed solution was prepared as follows: 0.02564 g of magnesium nitrate hexahydrate was dissolved in 10 mL of deionized water to obtain a magnesium nitrate solution, 0.6007 g of urea was dissolved in 10 mL of deionized water to obtain a urea solution, and then 0.1 mmol of the magnesium nitrate solution and 0.5 mmol of the urea solution were mixed, and deionized water was added to make the volume to 60 mL to obtain a modified mixed solution.

[0049] S3, preparation of Pd / Mg-NF: The Mg-NF matrix obtained in S2 was placed in a hydrothermal reactor with a volume of 100 ml, and a loaded mixed solution of a metal Pd salt solution and a precipitant was prepared. The loaded mixed solution was added into the hydrothermal reactor for ultrasonic mixing for 10 min, and then the hydrothermal reactor was placed in a 100°C oven for reaction for 1 h. After the reaction was completed, it was naturally cooled. The cooled product was washed and transferred to a 60°C oven for drying for 1 h to obtain an integral supported palladium-based catalyst Pd / Mg-NF.

[0050] The preparation method of the loaded mixed solution is as follows: dissolve 1 g of palladium nitrate dihydrate in 500 g of deionized water to obtain a palladium nitrate solution, dissolve 0.6007 g of urea in 10 mL of deionized water to obtain a urea solution, mix 1.5 mL of the palladium nitrate solution and 0.5 mmol of the urea solution, add deionized water to make the volume to 60 mL to obtain a loaded mixed solution.

[0051] Example 2

[0052] A method for preparing a monolithic supported palladium-based catalyst comprises the following steps:

[0053] S1. NF carrier pretreatment: select NF disc raw material with a diameter of 32 mm and a thickness of 1 mm, immerse it in an acetone solution for ultrasonic treatment for 20 minutes, then take out the NF and rinse it with deionized water for 5 times, then place the NF in a hydrochloric acid solution with a concentration of 1 mol / L for ultrasonic treatment for 10 minutes, then take out the NF and rinse it with deionized water for 5 times, finally place the NF in an anhydrous ethanol solution for ultrasonic treatment for 20 minutes to clean the oil impurities and residual substances on the surface, and dry it in an oven at 75°C for 3 hours to obtain the treated NF carrier, wherein the acetone solution, hydrochloric acid solution, and anhydrous ethanol solution are directly used as the corresponding products purchased without further treatment.

[0054] S2. Preparation of Mg-NF matrix: Take 5 pieces of NF carriers obtained in S1 and place them in a hydrothermal reactor with a volume of 100 ml, prepare a modified mixed solution of metal Mg salt solution and precipitant, add the modified mixed solution into the hydrothermal reactor for ultrasonic mixing for 20 minutes, and then place the hydrothermal reactor in a 160°C oven to react for 6 hours. After the reaction is completed, cool it naturally. After the cooled product is washed, place it in a 75°C oven and dry it for 3 hours to obtain the Mg-NF matrix.

[0055] The modified mixed solution was prepared as follows: 0.1282 g of magnesium nitrate hexahydrate was dissolved in 20 mL of deionized water to obtain a magnesium nitrate solution, 1.8021 g of urea was dissolved in 30 mL of deionized water to obtain a urea solution, and then 0.1 mmol of the magnesium nitrate solution and 0.5 mmol of the urea solution were mixed, and deionized water was added to make the volume to 80 mL to obtain a modified mixed solution.

[0056] S3, preparation of Pd / Mg-NF: The Mg-NF matrix obtained in S2 was placed in a hydrothermal reactor with a volume of 100 ml, and a loaded mixed solution of a metal Pd salt solution and a precipitant was prepared. The loaded mixed solution was added into the hydrothermal reactor for ultrasonic mixing for 20 min, and then the hydrothermal reactor was placed in an oven at 160°C for reaction for 6 h. After the reaction was completed, it was naturally cooled. The cooled product was washed and transferred to an oven at 75°C for drying for 3 h to obtain an integral supported palladium-based catalyst Pd / Mg-NF.

[0057] The preparation method of the loaded mixed solution is as follows: dissolve 1 g of palladium nitrate dihydrate in 500 g of deionized water to obtain a palladium nitrate solution, dissolve 1.8021 g of urea in 30 mL of deionized water to obtain a urea solution, mix 3 ml of the palladium nitrate solution and 1.5 mmol of the urea solution, add deionized water to make the volume to 80 mL to obtain a loaded mixed solution.

[0058] Example 3

[0059] A method for preparing a monolithic supported palladium-based catalyst comprises the following steps:

[0060] S1. NF carrier pretreatment: NF disc raw material with a diameter of 32 mm and a thickness of 1 mm was selected, immersed in an acetone solution for ultrasonic treatment for 30 min, then the NF was taken out and rinsed with deionized water for 5 times, and then the NF was placed in a 2 mol / L hydrochloric acid solution for ultrasonic treatment for 20 min, then the NF was taken out and washed with deionized water for 5 times, and finally the NF was placed in an anhydrous ethanol solution for ultrasonic treatment for 30 min to clean the oil impurities on the surface, and dried in an oven at 90°C for 5 h to obtain the treated NF carrier, wherein the acetone solution, the hydrochloric acid solution, and the anhydrous ethanol solution were directly used as the corresponding products purchased without further treatment.

[0061] S2. Preparation of Mg-NF matrix: Take 10 pieces of NF carriers obtained in S1 and place them in a hydrothermal reactor with a volume of 100 ml, prepare a modified mixed solution of metal Mg salt solution and precipitant, add the modified mixed solution into the hydrothermal reactor for ultrasonic mixing for 30 minutes, and then place the hydrothermal reactor in a 200°C oven to react for 10 hours. After the reaction is completed, cool it naturally. After the cooled product is washed, place it in a 90°C oven and dry it for 5 hours to obtain the Mg-NF matrix.

[0062] The modified mixed solution was prepared as follows: 0.2564 g of magnesium nitrate hexahydrate was dissolved in 30 mL of deionized water to obtain a magnesium nitrate solution, 2.4028 g of urea was dissolved in 40 mL of deionized water to obtain a urea solution, 1 mmol of the magnesium nitrate solution and 2 mmol of the urea solution were mixed, and deionized water was added to make the volume to 90 mL to obtain a modified mixed solution.

[0063] S3, preparation of Pd / Mg-NF: Take 10 pieces of Mg-NF matrix obtained in S2 and place them in a hydrothermal reactor with a volume of 100 ml, prepare a loaded mixed solution of metal Pd salt solution and precipitant, add the loaded mixed solution into the hydrothermal reactor for ultrasonic mixing for 30 minutes, and then place the hydrothermal reactor in a 200°C oven to react for 10 hours. After the reaction is completed, cool it naturally. After cooling, wash the product and transfer it to a 90°C oven for drying. After drying for 5 hours, the integral loaded palladium-based catalyst Pd / Mg-NF is obtained.

[0064] The preparation method of the loaded mixed solution is as follows: dissolve 1 g of palladium nitrate dihydrate in 500 g of deionized water to obtain a palladium nitrate solution, dissolve 2.4028 g of urea in 40 mL of deionized water to obtain a urea solution, mix 4.5 mL of the palladium nitrate solution and 2 mmol of the urea solution, add deionized water to make up to 90 mL to obtain a loaded mixed solution.

[0065] The catalysts prepared in Examples 1-3 of the present application are used for catalytic combustion of methane in a fixed bed reactor device.

[0066] 2. Comparison

[0067] Comparative Example 1

[0068] A method for preparing a monolithic supported palladium-based catalyst is different from that of Example 2 in that there is no step S2, and step S3 is directly performed after step S1 to obtain a Pd-NF catalyst.

[0069] Comparative Example 2

[0070] A method for preparing a monolithic supported palladium-based catalyst is different from that of Example 2 in that the Pd / Mg-NF obtained in S3 is calcined at 300° C. for 4 h to obtain a Pd / Mg-NF 300 catalyst.

[0071] Comparative Example 3

[0072] A method for preparing a monolithic supported palladium-based catalyst is different from that of Example 2 in that the Pd / Mg-NF obtained in S3 is calcined at 500° C. for 4 h to obtain a Pd / Mg-NF 500 catalyst.

[0073] Comparative Example 4

[0074] A method for preparing a monolithic supported palladium-based catalyst is different from that of Example 2 in that the Pd / Mg-NF obtained in S3 is calcined at 800° C. for 4 h to obtain a Pd / Mg-NF 800 catalyst.

[0075] 3. Performance test experiments and results

[0076] 1. Catalyst methane catalytic combustion reaction activity test

[0077] The catalysts obtained from NF, Examples 1-3 and Comparative Examples 1-4 were tested for methane catalytic combustion activity, and the test method was as follows:

[0078] The test was carried out using a fixed bed reactor apparatus. A mixed gas containing 0.2 vol%-2 vol% CH4 and air was passed into a fixed bed reactor equipped with a catalyst at a total flow rate of 400 ml / min. The test temperature range was 200-800°C and the pressure was normal pressure. An online methane detector was connected to the gas outlet to calculate the conversion rate.

[0079] The CH4 conversion rate is calculated as follows:

[0080] CH4 conversion(%)={([CH4]in–[CH4]out) / [CH4]in}×100%

[0081] Where: [CH4]in, [CH4]out are the methane concentrations at the feed and reactor outlet, respectively.

[0082] When the catalysts obtained in Examples 1-3 were used for methane combustion reaction, complete conversion was achieved at a relatively low temperature. The conversion rate curve of methane at the same concentration is shown in FIG. Figure 1 As shown by Figure 1 It can be seen that the low-temperature catalytic activity of the catalyst obtained in Example 2 is better and is the best example. Therefore, the Pd / Mg-NF catalyst obtained in Example 2 was used for subsequent testing.

[0083] Example 2 The conversion rate curve of methane at different concentrations is as follows Figure 2 As shown by Figure 2It can be seen that under the conditions of methane content of 0.2vol%-2vol% and total flow rate of 400ml / min, methane can be completely catalytically burned at about 430℃-460℃. Therefore, when the catalyst prepared by this method is used for methane catalytic combustion, methane catalytic conversion at low temperature can be achieved, thereby improving catalyst performance.

[0084] The conversion curves of the catalysts obtained from NF, Example 2 and Comparative Example 1 at a methane concentration of 1 vol% are shown in FIG. Figure 3 As shown by Figure 3 It can be seen that when the catalyst prepared by the preparation method provided by the present invention is used for methane combustion reaction, complete conversion of methane can be achieved at about 450°C, and the catalytic effect is better than that of NF raw materials and unmodified Pd-NF catalysts under the same conditions. This is because the modification of the magnesium element can effectively prevent the spontaneous agglomeration of the palladium element to improve the subsequent dispersibility of the palladium. The nickel foam disc with a high surface area and porous structure is selected as a specific carrier to provide a uniformly distributed space for the subsequent loading of the precious metal palladium. The precious metal palladium is dispersed and stabilized through the strong interaction between the specific carrier and the metal active component, which not only promotes its high dispersion, but also improves the low-temperature catalytic activity.

[0085] The conversion curves of the catalysts obtained in Example 2 and Comparative Examples 2-4 at a methane concentration of 1 vol% are shown in FIG. Figure 4 As shown by Figure 4 It can be seen that the catalyst still has good catalytic performance after high-temperature calcination at 300°C and 500°C. If the calcination temperature is too high, it is easy to sinter.

[0086] 2. Appearance inspection

[0087] The appearance of the catalysts obtained from NF, Example 2 and Comparative Examples 1-4 were observed respectively. The physical appearance of the catalysts is shown in the figure below: Figure 5 As shown, from the color of the appearance, it can be seen that after only adding metal Pd, the comparative example 1 has obvious metallic luster, indicating that the metal Pd is evenly loaded on the NF. After adding metal Pd and metal Mg, the metallic luster of Example 2 is weakened compared with the comparative example 1, indicating that the metal Mg is successfully loaded. Comparative examples 2-4 are slightly black, indicating that sintering may have occurred.

[0088] 3. Structural Characterization

[0089] The Pd / Mg-NF catalyst of Example 2 before and after use was scanned by a scanning electron microscope + energy dispersive spectrometer to obtain a SEM-EDS graph. The scanning result before use is as follows: Figure 6 As shown, the scan results after use are as follows Figure 7 As shown, a scanning electron microscope was used to scan the state of the Pd / Mg-NF obtained in Example 2 before and after use to obtain a SEM image. The scanning result is as shown in FIG. Figure 8shown.

[0090] Depend on Figure 6-8 It can be seen that Mg and Pd are successfully loaded on the carrier NF. The Pd nanoparticles are evenly distributed on the NF surface before and after use, and the magnesium crystals grow evenly on the NF surface. No sintered large particles are seen in the microscopic morphology before and after use, and no agglomeration phenomenon occurs. Therefore, it is proved that the preparation method provided by the present invention effectively organizes the sintering of the catalyst. Figure 1-3 It was found that the modification of magnesium element can effectively prevent the spontaneous agglomeration of palladium element, so as to improve the subsequent dispersion of palladium. It is also beneficial to improve the atomic utilization efficiency of active components, and realize the catalytic conversion of methane at low temperature with a lower precious metal loading. The precious metal palladium is dispersed and stabilized through the strong interaction between specific carriers and metal active components, which can prevent the agglomeration and growth of metal components while promoting its high dispersion and improving low-temperature catalytic activity. The product has good reaction activity.

[0091] 4. Thermal stability test

[0092] The thermal stability of the catalysts obtained in Example 2 and Comparative Example 1 was tested respectively. The thermal stability comparison results of the catalysts obtained in Example 2 and Comparative Example 1 at 500°C are shown in the attached figure. Fig. 9 As shown by Fig. 9 It can be seen that the thermal stability of the catalyst obtained in Example 2 is much better than that of the catalyst obtained in Comparative Example 1. Figure 1-3 It was found that the strong interaction between the specific carrier nickel foam disc and the magnesium element dispersed and stabilized the precious metal palladium, which not only promoted its high dispersion and improved the low-temperature catalytic activity, but also prevented the agglomeration and growth of metal components. The product also had good reaction activity and stability.

[0093] 5. Performance comparison

[0094] The performance of the Pd / Mg-NF prepared in Example 2 was compared with that of the catalysts reported previously (see references 1-3). 90 To achieve a temperature of 90% conversion rate, thermal stability is related to the test temperature. The higher the test temperature, the easier the catalyst is to sinter. Testing at high temperature can better reflect thermal stability, that is, anti-sintering ability. By comparison, it is found that the performance of Pd / Mg-NF prepared in Example 2 is excellent, and its low-temperature catalytic activity and thermal stability exceed those of a large number of palladium-based catalysts reported in this field (see Table 2).

[0095] Table 2 Performance comparison of Example 2 and existing reports of palladium-based catalysts

[0096]

[0097]

[0098] In summary, through the characterization and performance measurement of Pd / Mg-NF, it can be concluded that when the Pd / Mg-NF catalyst prepared by this method is used for catalytic combustion of methane, it can completely catalyze the combustion of methane at about 430℃-460℃ under the conditions of methane content of 0.2vol%-2vol% and total flow rate of 400ml / min.

[0099] This method selects nickel foam NF as a specific carrier, and utilizes its porous structure characteristics with good thermal conductivity, thermal stability and high surface area to provide a uniformly distributed space for the subsequent loading of precious metal palladium. The nickel foam is modified by a metal magnesium solution. The modification of the magnesium element can effectively prevent the spontaneous agglomeration of the palladium element, so as to improve the subsequent dispersibility of palladium and improve the thermal stability of the catalyst, which is beneficial to improve the atomic utilization efficiency of the active component and realize the catalytic conversion of methane at low temperature with a lower precious metal loading. The precious metal palladium is dispersed and stabilized through the strong interaction between the specific carrier and the metal active component, which can prevent the agglomeration and growth of the metal component while promoting its high dispersion and improving the low-temperature catalytic activity. The product has both good reaction activity and stability. In addition, this method is simple to prepare, with mild conditions, controllable process, strong repeatability, and has good practical application prospects.

[0100] References 1-3 are as follows:

[0101] [1]Lin J, Xu Y, Chen

[0102] [2]Fazlikeshteli S,Vendrell

[0103] [3]Cai J,Wang J,Liu C,et al.Electron transferring with oxygen defectson Ni-promoted Pd / Al2O3 catalysts for low-temperature lean methane combustion[J].Journal of Colloid and InterfaceScience,2024.

Claims

1. A method for preparing a monolithic supported palladium-based catalyst, characterized in that: The method comprises the following steps: firstly, metallic magnesium is grown on NF to form a Mg-NF matrix, and then palladium is loaded on the matrix to prepare an integral supported palladium-based catalyst Pd / Mg-NF. S1. NF carrier pretreatment: select an appropriate amount of NF raw material and clean the oil impurities on the surface, and then dry to obtain the treated NF carrier; S2. Preparation of Mg-NF matrix: The NF carrier obtained in S1 is mixed with a metal Mg salt solution and a precipitant, and the mixed solution is placed in an oven for hydrothermal reaction, and taken out after natural cooling, and dried to obtain a Mg-NF matrix; S3, preparation of Pd / Mg-NF: The Mg-NF matrix obtained in S2 is mixed with a metal Pd salt solution and a precipitant, and the mixed solution is placed in an oven for hydrothermal reaction, and taken out after natural cooling, and dried to obtain an integral supported palladium-based catalyst Pd / Mg-NF.

2. The preparation method according to claim 1, characterized in that: The following steps are involved: S1. NF carrier pretreatment: select NF disc raw material with a diameter of 32 mm and a thickness of 1 mm, immerse it in an acetone solution for ultrasonic treatment for 10-30 minutes, then take out the NF and wash it with deionized water, then place the NF in a hydrochloric acid solution with a concentration of 0.2-2 mol / L and ultrasonically treat it for 2-20 minutes, then take out the NF and wash it with deionized water, finally place the NF in an anhydrous ethanol solution for ultrasonic treatment for 10-30 minutes to clean the oil impurities and residual solution on the surface, and transfer it to a 60-90°C oven for drying for 1-5 hours to obtain the treated NF carrier; S2, preparation of Mg-NF matrix: take 1-10 pieces of NF carrier obtained in S1 and place them in a hydrothermal reactor, prepare a modified mixed solution of metal Mg salt solution and precipitant, add the modified mixed solution into the hydrothermal reactor for ultrasonic mixing for 10-30 minutes, then place the hydrothermal reactor in a 100-200°C oven for reaction for 1-10 hours, cool naturally after the reaction is completed, wash the cooled product and place it in a 60-90°C oven for drying for 1-5 hours to obtain a Mg-NF matrix, wherein the modified mixed solution is prepared as follows: dissolve 0.1-1 mmol of metal Mg salt solution and 0.5-2 mmol of precipitant in 60-90 mL of deionized water, wherein the metal Mg salt solution is a magnesium nitrate solution, and the precipitant is a urea solution; S3, preparation of Pd / Mg-NF: placing the Mg-NF matrix obtained in S2 in a hydrothermal reactor, preparing a loaded mixed solution of a metal Pd salt solution and a precipitant, adding the loaded mixed solution into the hydrothermal reactor for ultrasonic mixing for 10-30 minutes, and then placing the hydrothermal reactor in a 100-200°C oven for reaction for 1-10 hours. After the reaction is completed, the reaction is naturally cooled. After the cooled product is washed, it is transferred to a 60-90°C oven for drying for 1-5 hours to obtain an integral loaded palladium-based catalyst Pd / Mg-NF. The loaded mixed solution is prepared as follows: 1.5-4.5 ml of a metal Pd salt solution and 0.5-2 mmol of a precipitant are dissolved in 60-90 mL of deionized water, wherein the metal Pd salt solution is a palladium nitrate solution, and the precipitant is a urea solution.

3. The preparation method according to claim 2, characterized in that: S1. NF carrier pretreatment: Select NF disc raw materials with a diameter of 32 mm and a thickness of 1 mm, immerse them in an acetone solution for ultrasonic treatment for 20 minutes, then take out the NF and rinse it with deionized water for 5 times, then place the NF in a 1 mol / L hydrochloric acid solution for ultrasonic treatment for 10 minutes, then take out the NF and rinse it with deionized water for 5 times, finally place the NF in an anhydrous ethanol solution for ultrasonic treatment for 20 minutes to clean the oil impurities on the surface, and dry it in an oven at 75°C for 3 hours to obtain the treated NF carrier.

4. The preparation method according to claim 2, characterized in that: S2. Preparation of Mg-NF matrix: Take 5 pieces of NF carrier obtained in S1 and place them in a hydrothermal reactor with a volume of 100 ml, prepare a modified mixed solution of metal Mg salt solution and precipitant, add the modified mixed solution into the hydrothermal reactor for ultrasonic mixing for 20 minutes, and then place the hydrothermal reactor in a 160°C oven for reaction for 6 hours. After the reaction is completed, cool naturally. After the cooled product is washed, place it in an oven at 75°C for drying for 3 hours. After drying, Mg-NF matrix is ​​obtained. The preparation method of the modified mixed solution is as follows: after mixing 0.5 mmol of magnesium nitrate solution and 1.5 mmol of urea solution, add deionized water to make the volume to 80 mL.

5. The preparation method according to claim 1, characterized in that: S3, preparation of Pd / Mg-NF: Take 5 pieces of Mg-NF matrix obtained in S2 and place them in a hydrothermal reactor with a volume of 100 ml, prepare a loaded mixed solution of metal Pd salt solution and precipitant, add the loaded mixed solution into the hydrothermal reactor for ultrasonic mixing for 20 minutes, and then place the hydrothermal reactor in a 160°C oven to react for 6 hours. After the reaction is completed, it is naturally cooled. After the cooling product is washed, it is transferred to a 75°C oven for drying for 3 hours. After drying, an integral loaded palladium-based catalyst Pd / Mg-NF is obtained. The configuration method of the loaded mixed solution is as follows: 3 mL of palladium nitrate solution and 1.5 mmol of urea solution are dissolved in 80 mL, mixed, and deionized water is added to make the volume to 80 mL.

6. The preparation method according to claim 1, characterized in that: In S2, the magnesium nitrate solution is obtained by dissolving 0.1282 g of magnesium nitrate hexahydrate in deionized water.

7. The preparation method according to claim 1, characterized in that: In S3, the palladium nitrate solution is obtained by dissolving 1 g of palladium nitrate dihydrate in 500 g of deionized water.

8. The preparation method according to claim 1, characterized in that: In S3, the urea solution is obtained by dissolving 1.8021 g of urea in deionized water.

9. A monolithic supported palladium-based catalyst, characterized in that: The preparation method is described in any one of claims 1 to 8.

10. Use of the monolithic supported palladium-based catalyst according to claim 9 in catalytic combustion of methane.

Citation Information

Patent Citations

  • Low-concentration methane catalytic combustion catalyst and preparation method of the same

    CN103131488A

  • Integrally-used palladium catalyst, preparation method and application thereof

    CN103977813A

  • Surface strengthening-type palladium-based catalyst for catalytic combustion of low concentration methane and preparation method thereof

    CN105457653A

  • Preparation method of catalyst for CO gas-phase catalyzed synthesis of dimethyl oxalate

    CN105597743A

  • Catalyst for carbon monoxide gas-phase catalytic synthesis of dimethyl oxalate and preparation method and application thereof

    CN105688934A